The armed forces of UN peacekeeping and Ukraine's participation in peacekeeping operations - Svitlana Libruk-Lipkevych (Cхід, 2013)
Structural relations betweenUkraineand UN which is based on the mutual understanding and readiness for collaboration on questions of peace maintenance in the world problem regions, are considered in the article.